Praktik Raja Yoga Dalam Rangkaian Pementasan Barong Brutuk Di Desa Terunyan, Kintamani, Bangli: Studi Teologi Hindu Dalam Terminologi Kearifan Lokal - Sabda Jayendra, Putu (PANGKAJA: JURNAL AGAMA HINDU, 2018)
Raja Yoga is a method to connect one’s self to the almighty God (Ida Sang Hyang Widhi Wasa) through the means of tapa, brata, yoga, semadhi. This method is conceptualized in Astangga Yoga passed down by Rsi Patanjali. Terminologically, the practice of Raja Yoga is covered in local genius existed in Terunyan village, Bangli regency. It is done by the so called Teruna (a group of teenagers) as a part of sacred procession of Barong Brutuk dance. Essentially, Raja yoga can be seen in the Makemit process for 42 days with a set of rules, prohibition, and ritu- al they call Tirtha Kayan Teruna. The success of the Raja Yoga according to local condition is when the teruna achieves niyasa, or a condition where the body and soul become one with God in its system, not overtaking the trance as other sacred dances do in Bali.